NF-κB synergizes with NF-AT and NF-IL6 in activation of the IL-4 gene in T cells - Li-Weber, Min; Giaisi, Marco; Baumann, Sven; Pálfi, Katalin; Krammer, Peter H. (European journal of immunology, 2004)
IL-4 plays a pivotal role in the development of the Th2 cell mediated humoral immune response and causes IgE-dependent allergic inflammatory diseases. Expression of IL-4 in differentiated Th2 cells is regulated by transcription factors such as NF-AT, AP-1 and NF-IL6. Recently, increasing evidence indicates that the pro-inflammatory transcription factor NF-κB may also participate inIL-4 expression. In this study, we show that the IL-4 promoter is synergistically activated by NF-κB, NF-AT and NF-IL6 at the NF-κB/NF-AT/NF-IL6 composite sites. In addition, we performed the chromatin immunoprecipitation technique to determine the functional relevance of NF-κB in the activation of the IL-4 gene in vivo. We demonstrate that NF-κB binds to the IL-4 promoter in vivo upon T cell activation. Inhibition of NF-κB nuclear translocation in living cells blocked binding of NF-κB to the IL-4 promoter. The data provide first evidence that NF-κB is directly involved in IL-4 transcription.
Gesehen am 04.03.2021